Pesan Moral Dalam Iklan Bibit Versi “Suara Hati Generasi Sandwich” : Analisis Semiotika Charles Sanders Pierce - Irsyad Renaldi; Daniel Handoko (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Advertising is a form of non-personal presentation and promotion of ideas, goods, or services by certain parties that are required to pay to spread the desired message, it can also be to build preferences to educate people or brands, forms of advertising can be in the form of electronic media and print media, magazines etc.. The advertising communication contains information about the existence of the product through images, words, writing and sound processed with an attractive display to encourage the audience to make purchases of the advertised product and so that the attractiveness of this advertisement is more able to influence the audience This study aims to identify signs and analyze the moral messages contained in the Bibit advertisement version "Suara Hati Generasi Sandwich" aired on the Bibit Youtube account, analyzing this advertisement using Charles Sanders Peirce semiotic analysis. The qualitative approach is descriptive with data collection using document analysis and literature study. This research wants to examine the moral messages contained in the Bibit advertisement version of "Suara Hati Generasi Sandwich" with the Triangle of Meaning, namely Sign, Object, and Interpretant. Based on the research results, the signs in this advertisement are Sign, Object, and Interpretant which identify that this advertisement is intended for people who want to invest in order to have assets that will be useful in the future. There are two messages in this advertisement, namely verbal and non-verbal messages. The verbal message is a Voice Over narration in the ad is to keep thinking about things that may not be thought of by us now and must prepare because anything can happen. While non-verbal messages are all expressions and background settings in several scenes. The moral message in this advertisement is to teach filial piety to parents, teach responsibility and teach to be financially literate.